Budaya Berhuni Kaum Sufistik Borjuis: Kontestasi Simbolik dalam Konstruksi Rumah Adat Kudus - Said, Nur (UIN Maulana Malik Ibrahim Malang, 2008)
Omah, Javanese term for house, is not only as a place to protect from hot and cold weather, importantly, as a place for Javanese people to actualize themselves both personally and socially. This is interesting to expose as its existence represents the symbolic fight of negotiation process between cultures happened in its period. The relationship between the house and its occupant symbolizes the cultural apprenticeship which is expressed in the use of the room. The house also represents the substance and material aspect, even, the first one still becomes the main concern. The substance aspect can be seen in the ornament which sometimes still has animal picture, as Sunan Kudus is someone who has high tolerance. The material aspect expresses the strategy to defend the existence and dignity. As a whole, the house represents the face of Islam which is substantive-esoteric, and still considers existentialist-symbolic aspect as another important aspect. Omah, istilah Jawa untuk rumah, tidak hanya sebagai tempat untuk melindungi dari cuaca panas dan dingin, yang penting, sebagai tempat bagi orang Jawa untuk mengaktualisasikan diri mereka baik secara pribadi maupun sosial. Hal ini menarik untuk diungkapkan karena keberadaannya merupakan pertarungan simbolis dalam proses negosiasi antara budaya yang terjadi pada periode tersebut. Hubungan antara rumah dan penghuninya melambangkan magang budaya yang diungkapkan dalam penggunaan ruangan. Rumah juga mewakili substansi dan aspek material, bahkan yang pertama tetap menjadi perhatian utama. Aspek substansi bisa dilihat pada ornamen yang terkadang masih memiliki gambar binatang, karena Sunan Kudus adalah seseorang yang memiliki toleransi tinggi. Aspek material mengekspresikan strategi untuk mempertahankan eksistensi dan martabat. Secara keseluruhan, rumah tersebut mewakili wajah Islam yang bersifat substantif-esoteris, dan masih menganggap aspek eksistensialis-simbolis sebagai aspek penting lainnya.